Diagnosis of pupillary block glaucoma after removal of congenital cataracts with intraoperative ultrasound biomicroscopy: a case report. Issue 1 (December 2016) - Zhu, Xiang-Jia; Zhang, Ke-Ke; He, Wen-Wen; Sun, Xing-Huai; Meng, Fan-Rong; Lu, Yi
Abstract Background Aphakic glaucoma is a common complication after congenital cataract extraction, especially in those who have surgery during infancy. This case report describes a case of bilateral pupillary block glaucoma diagnosed with intraoperative ultrasound biomicroscopy (UBM) after removal of congenital cataract. Case presentation We present a case report of a 9-month-old infant with bilateral corneal enlargement and ocular hypertension after uneventful removal of congenital cataracts. Initial and follow-up examination findings were reviewed. The infant was suspected to have developmental glaucoma and schemed to have bilateral trabeculotomy until pupillary obstruction by vitreous herniation and angle closure with iris bombé were detected by intraoperative UBM. Anterior vitrectomy and goniosynechialysis were then performed as treatment. Conclusion Pupillary block glaucoma is a rare type of infantile aphakic glaucoma. Application of intraoperative UBM can assist in the differential diagnosis of aphakic glaucoma in infants.